Men's and Women's Language Features Used by The Characters in The Do Revenge (2022) Movie by Jennifer Kaytin Robinson - Nur Hikmah Afief; Yana Qomariana; Ni Made Ayu Widiastuti (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2023)
It is said that men and women communicate differently, attaching different meanings to the same words. Men speak in concrete words to convey information, while women use artistic license and dramatic vocabulary to express and convey their feelings. Therefore, this research aims to (1) identify men's and women’s language features used by the characters in the Do Revenge movie and (2) examine the factors that influence the differences in language use between men and women. This research applied the theory from Lakoff (1975) about women’s language features and factors that influence the differences in language use between men and women, and Coates (2013) about men’s language. The data source is taken from a movie entitled Do Revenge (2022) directed by Jennifer Kaytin Robinson. The researcher got the data from the dialogue of males and females characters. The qualitative research method was used to analyze the data in this study. The technique of data analysis is the descriptive method. The findings show that female characters showed 9 out of 10 women’s language features in total 175. They were lexical hedges or fillers, avoidance of strong swear words, empty adjectives, intensifiers, tag questions, rising intonation on declarative, hypercorrect grammar, emphatic stress, and super polite forms. On the other side, male characters showed 4 out of 5 men’s language features in total 37. They were minimal responses, the use of swearing and taboo language, commands and directives, and question. The researcher also found that psychology and social status are factors that affect the differences in the language of women and men in the Do Revenge movie.